2009
DOI: 10.1080/10495390903209928
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Yak MUC1 Protein Polymorphisms and the Corresponding VNTR Structure

Abstract: The genotypes and protein polymorphisms of milk epithelial mucin (MUC1) were analyzed by touch-down PCR and SDS-PAGE respectively using blood samples and milk collected from 50 lactating yaks. A total of seven alleles were revealed, namely A, B, C, D, E, F, and G, and the corresponding number of repetitive units of variable number tandem repeat (VNTR) in MUC1 gene were 21, 20, 19, 18, 17, 16, and 15, respectively. Fifteen genotypes of MUC1 were observed in yaks. The genotypes of MUC1 gene matched completely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In humans, the number of repeats at the VNTR region ranges from 25 and 125 with size ranging from 1,000-5,000 bp (Ando et al 1998). In ruminants, the VNTR region varied from 1,500-3,000 bp in goats (Sacchi et al 2004), from 778 to 1894bp in bovines (Rasero et al 2002;Souza et al 2007;Sando et al 2009), four alleles of approximately 1500 bp in sheep (Rasero et al 2007) and from 1206 to 1566 bp in yaks (Zheng et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the number of repeats at the VNTR region ranges from 25 and 125 with size ranging from 1,000-5,000 bp (Ando et al 1998). In ruminants, the VNTR region varied from 1,500-3,000 bp in goats (Sacchi et al 2004), from 778 to 1894bp in bovines (Rasero et al 2002;Souza et al 2007;Sando et al 2009), four alleles of approximately 1500 bp in sheep (Rasero et al 2007) and from 1206 to 1566 bp in yaks (Zheng et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we examined four SNPs, published earlier by Madsen and coworkers 42 , in 29 Polish Landrace × Duroc, Pietrain crossbreed pigs. We found that in the Polish Landrace crossbreed with Duroc × Pietrain, for SNP 594 C > G, 86% of pigs had the SNP (CG or GG) predisposing to increased amount of lumbar back fat, total percentage of lipids, and intramuscular fatness 4 . This may explain why we were successful in obtaining a high level of fatness and observed the development of insulin resistance in the group of pigs fed the HE diet.…”
Section: Discussionmentioning
confidence: 82%
“…In recent years, a few studies have been published on porcine SNPs in the FTO gene. Interestingly, an association of SNPs with intramuscular fat deposition has been found in pigs such as the Italian Duroc, the Danish commercial pig, as well as the Gottingen minipig 4 , 42 , 44 46 . In our study, we examined four SNPs, published earlier by Madsen and coworkers 42 , in 29 Polish Landrace × Duroc, Pietrain crossbreed pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation